Bullying in Primary School Pupils / 1st Kurk and Its Relationship with Gender - Jassem, Mustafa; Mohsen, Nuha (Journal of Physical Education, 2020)
The research aimed at identifying bullying in primary school pupils and comparing it with other students according to gender. The researchers used the descriptive method on (199) students from Al Munsoor primary school all aged (11) for the year 2019 – 2020. Male pupils were (100) and female pupils were (99). School bullying scale, that consisted of (45) item, was selected and after being reviewed by a group of experts in educational psychology, many items were deleted leaving only (29) items. The scale was applied on the school pupils to conclude that bullying in male is higher than female pupils.